Comprehensive analysis of human monocyte subsets using full-spectrum flow cytometry and hierarchical marker clustering - Li, Chao; Xiao, Maozhi; Geng, Suxia; Wang, Yulian; Zeng, Lingji; Lai, Peilong; Gong, Ying; Chen, Xiaomei (Frontiers in Immunology, 2024)
Exploring monocytes' roles within the tumor microenvironment is crucial for crafting targeted cancer treatments. This study unveils a novel methodology utilizing four 20-color flow cytometry panels for comprehensive peripheral immune system phenotyping, specifically targeting classical, intermediate, and non-classical monocyte subsets. By applying advanced dimensionality reduction techniques like t-distributed stochastic neighbor embedding (tSNE) and FlowSom analysis, we performed an extensive profiling of monocytes, assessing 50 unique cell surface markers related to a wide range of immunological functions, including activation, differentiation, and immune checkpoint regulation. This in-depth approach significantly refines the identification of monocyte subsets, directly supporting the development of personalized immunotherapies and enhancing diagnostic precision. Our pioneering panel for monocyte phenotyping marks a substantial leap in understanding monocyte biology, with profound implications for the accuracy of disease diagnostics and the success of checkpoint-inhibitor therapies. Key findings include revealing distinct marker expression patterns linked to tumor progression and providing new avenues for targeted therapeutic interventions.